Ask a New Question
Search
solve by the gauss-jordan method
Use the Gauss-Jordan method to find all the solutions of the system
-3x1 +2x2 -x3 +6x4 = -7 7x1 -3x2 +2x3 -11x4 = 14 x1 -x4 = 1
5 answers
asked by
Cladis
1,723 views
Solve for x,y,z, & w using the Gauss-Jordan Elimination Method
5x+3y+z+5w=-2 3x+2y+2z+4w=2 2x+4y+3z-3w=-11 4x-3y-2z+2w=-3 Can
1 answer
asked by
Linda
1,038 views
solve by the gauss-jordan method
x+y+z=6 3x+2y-z=4 3x+2y+2z=11
1 answer
asked by
Diahann
533 views
solve using the gauss-jordan method.
x-2y+4z=7 -x+3y-z=-1 2x+y=-2 *I get through the first two columbs, but can't get the third
3 answers
asked by
Veronica
505 views
Use the Gauss-Jordan method to solve the equation:
3x-5y-2z=-9 -4x+3y+z=11 8x-5y+4z=6
1 answer
asked by
Andrew
641 views
Solve this equation using the Gauss Jordan elimination method.
x + y - z = 7 x - y + 2z = 3 2x + y + z = 9
1 answer
61 views
Solve using Gauss Jordan method - Write in terms of (x, y, z) = ( )
3y + 2z = 1 2x − y − 3z = 3 2x + 2y − z = 4
0 answers
asked by
Anon
547 views
Solve this equation using the Gauss Jordan elimination method.
4x - y + 2z = 13 x + 2y - 2z = 0 -x + y + z = 5
1 answer
52 views
How would you solve this matrices using the Gauss-jordan elimination method?
{[-5, 8, 10]} {[5, 8, 4]} {[10, 8, 5]} {[5, 4, 8]}
2 answers
asked by
Jesse
584 views
4x - y + 2z = 13
x + 2y - 2z = 0 -x + y + z = 5 Solve the above equation using the Gauss Jordan elimination method.
1 answer
54 views